The Graying of Academia Will It Reduce Scientific Productivity? - Wolfgang Stroebe (Center for Research in Economics, Management and the Arts (CREMA), 2014)
The belief that science is a young person's game and that only young scientists can be productive and publish highquality research is still widely shared by university administrators and members of the scientific community. Since the average age of university faculties is increasing not only in the United States but also in Europe, the question arises as to whether this belief is correct. If it were valid, the abolition of compulsory retirement in the United States and some parts of Canada would lower the productivity of these university systems. To address this question, this article reviews research on the association of age and scientific productivity conducted during the last four decades in North America and Europe. Whereas early research typically showed a decline in productivity after the ages of 40 to 45 years, this decline has been absent in more recent studies. Explanations for this change are discussed.
Keywords: 330; academic productivity; scientific achievement; age discrimination; creative potential